Basta Brussel Nieuwsbrief. - Basta! (Brussel : Basta!, 1988)
Fonds Suzan Daniel (FSD)
Vanaf 3(1999) 1 : Basta Nieuwsbrief
Periodiciteit : tweemaandelijks
Redactie : postbus 1696, 1000 Brussel
Nederlands
Periodiek
Keywords: Holebibladen